Spectroscopic Evidence in Solid and Solution of a Discrete Copper(I) Tetrahedral Complex Dimer Supported by Supramolecular Interactions - Guerrero-Nunez, J; Guerrero-Nunez, J; Lemus-Chavez, L; Lemus-Chavez, L (2012)
The first study of the self-association of a copper(I) tetrahedral complex ([Cu(N-{4-nitrophenyl}pyridine-2-yl-methanimine)(PPh 3)Br]) has been performed. The formation of a discrete dimer supported by supramolecular ?-? stacking and C-H·Br interactions was established by X-ray diffraction techniques. 1D- and 2D NMR techniques were used for the structural characterization of this compound in solution. Unexpected 1H- 1H NOE effects are coherent with the presence of a dimer in solution, whose structure replicates that found in the crystal. Dimerization constants obtained by VT- 1H NMR spectroscopy allowed the determination ofthe thermodynamic parameters for the self-association process, namely ?S = -0.67±0.21 calmol -1K -1, ?H = -2.00±0.05 kcalmol -1 and ?G(298 K) = -1.79 kcalmol -1. Consequently, this association process is enthalpy driven. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.